2020
DOI: 10.1002/ejoc.202000746
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Photocatalytic Functionalization of Quinoxalin‐2‐ones

Abstract: Visible-light-mediated chemical reactions have become highly popular in the last ten years. This review covers the recent developments in visible-light photofunctionalization of quinoxalin-2-one derivatives. Reaction types have been categorized depending on the kind of bond formed: CC , CO , [a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 80 publications
(32 citation statements)
references
References 141 publications
(111 reference statements)
0
30
0
Order By: Relevance
“…These photophysical study results encouraged us to further evaluate the photochemical application of the excited C(2)-benzoyl-substituted benzothiazoline (1a*). Considering the importance of C(3)-substituted quinoxalin-2-ones [44,45], we selected photo-promoted structural modification of quinoxalin-2-one as a model reaction. It was found that the mixture of 1a with quinoxalin-2-one 2a under the sole irradiation of blue LED in CHCl3 after These photophysical study results encouraged us to further evaluate the photochemical application of the excited C(2)-benzoyl-substituted benzothiazoline (1a*).…”
Section: Photophysical Property Of Benzothiazolinesmentioning
confidence: 99%
See 1 more Smart Citation
“…These photophysical study results encouraged us to further evaluate the photochemical application of the excited C(2)-benzoyl-substituted benzothiazoline (1a*). Considering the importance of C(3)-substituted quinoxalin-2-ones [44,45], we selected photo-promoted structural modification of quinoxalin-2-one as a model reaction. It was found that the mixture of 1a with quinoxalin-2-one 2a under the sole irradiation of blue LED in CHCl3 after These photophysical study results encouraged us to further evaluate the photochemical application of the excited C(2)-benzoyl-substituted benzothiazoline (1a*).…”
Section: Photophysical Property Of Benzothiazolinesmentioning
confidence: 99%
“…It was found that the mixture of 1a with quinoxalin-2-one 2a under the sole irradiation of blue LED in CHCl3 after These photophysical study results encouraged us to further evaluate the photochemical application of the excited C(2)-benzoyl-substituted benzothiazoline (1a*). Considering the importance of C(3)-substituted quinoxalin-2-ones [44,45], we selected photo-promoted structural modification of quinoxalin-2-one as a model reaction. It was found that the mixture of 1a with quinoxalin-2-one 2a under the sole irradiation of blue LED in CHCl 3 after 4 h led to the desired C3-acylated product 3aa in 38% isolated yield (Figure 1d).…”
Section: Photophysical Property Of Benzothiazolinesmentioning
confidence: 99%
“…Quinoxalin-2­(1 H )-ones are widely present in numerous bioactive natural products and pharmaceuticals because of their significant biological activities and outstanding chemical properties (Scheme a). , Direct functionalization of quinoxalin-2­(1 H )-ones, especially at the C3 position, is a convenient method to expand their structural diversity. In recent years, impressive advances have been made to access 3-substituted quinoxalin-2­(1 H )-ones through transition-metal-catalyzed or visible light-induced functionalization, including arylation, acylation, phosphonation, amination, or trifluoromethylation (Scheme a) . Despite that a range of functionalized quinoxalin-2­(1 H )-ones have been prepared, the structural complexity and chemical space for this class of hetereocycles are still highly expected to be expanded by exploiting new synthetic pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Gratifyingly, the target product tert -butyl (4-methyl-3- oxo -3,4-dihydroquinoxalin-2-yl)­carbamate ( 3a ) was obtained in 66% yield under irradiation of 30 W blue LEDs without adding any photocatalyst. Notably, such nitrogen-containing heterocycles are widely encountered in natural products and pharmaceuticals with a range of biological activities . To shed more light on the nature of the present reaction, further control experiments were launched.…”
mentioning
confidence: 99%